Enhancements of mass transfer and heat transfer by microreactors and their applications in chemical engineering - ZHANG Shikai; LUO Canghai; ZHENG Yuan; XIAO Yao; CHEN Dong* (能源环境保护)
Chemical reactions involving fine chemicals, environmental protection, and chemical drugs often necessitate continuous operation, high selectivity, and utmost safety. Particularly, when dealing with strong exothermic reactions, improper control can lead to fire or even explosions. Enhancements in mass transfer and heat transfer are crucial for addressing these challenges. Microreactors, in comparison to conventional tank reactors, offer several advantages, including high mass and heat transfer efficiency, precise control of reaction parameters, continuous operation, and enhanced efficiency and safety. This review provides a comprehensive summary of research on microreactors in chemical engineering. First, the structural characteristics and advantages of microreactors are analyzed. Next, the strategies employed in the design of microreactors to enhance mass and heat transfer are summarized. The applications of microreactors in typical strong exothermic reactions are then introduced. Finally, the review concludes by highlighting the importance, opportunities, and challenges associated with microreactor technology. The objective of this review is to provide guidance for the design, manufacturing, and application of microreactors in the industry.